Physicochemical attributes, antioxidant activity, and sensory responses of low-fat cheese supplemented with spray-dried Jamun juice (Syzygium cumini L.) powder - Shelke, Ganesh N.; Kad, Vikram P.; Yenge, Govind B.; Kukde, Ritu B.; Kakade, Sudama R.; Al-Dalain, Sati Y.; Haddad, Moawiya A.; Abdeen, Ahmed; Ibrahim, Samah F.; Abdelkhalek, Adel; Imbrea, Florin; Fericean, Liana; et al. (Frontiers in Sustainable Food Systems, 2023)
The current work aimed to enhance the quality, antioxidant activity, and sensory properties of low-fat soft cheese using Jamun Juice (Syzygium cumini L.) powder (JJP). Spray-dried JJP was added to soft cheese at four concentrations (4, 8, 12, and 16% w/v), in parallel to a control sample. The bioactive compounds of spray-dried JJP including total anthocyanin content (TAC), total phenolic content (TPC), ascorbic acid (AsA), and antioxidant ability (AA) were determined. The physicochemical, functional, color, textural, and organoleptic quality of cheese were estimated. Results revealed that JJP had a rich in contents of TAC 10.72 mg/g, TPC 22.08 mg/g, AsA 0.32 mg/g, and antioxidants 62.66%. The low-fat cheese included 16% JJP was high in moisture and ash contents while low in protein and pH compared to other treatments and control. The low-fat cheese included 16% JJP was high in TAC 0.22 mg/g, TPC 0.80 mg/g, AsA 0.056 mg/g, and AA 40.08%, compared to cheese contained JJP 4%–12%. The color attributes L*, a*, and b* of soft cheese-based 12% JJP were enhanced. Spray-dried JJP at 12% and 16% significantly affected textural profile, like firmness, cohesiveness, adhesiveness, springiness, gumminess, and chewiness of soft cheese compared to other samples. The 12% and 16% JJP improved the sensory acceptability of soft cheese treatments. The findings demonstrated that JJP at 12% could be a promising replacing material enriched with antioxidant and anthocyanin contents and help improve the quality and acceptability of low-fat soft cheese.